Pengembangan Sistem Informasi Akuntansi untuk Proses Produksi pada PT. Xyz - Kurniawan, Yohannes; Luhukay, Devyano; Halim, Titan (Bina Nusantara University, 2014)
The purpose of the research is to identify and analyze the need of accounting information system for processes, procedures, and documents related to the production process at PT XYZ, which design the useful of accounting information systems to support business processes that occur. The design method used in this research is a method of Object Oriented Analysis and Design (OOAD) with the UML notation, including: use case diagram, class diagram, and component architecture. Analyzes performed related to the organizational structure and business processes based on the theory of accounting information systems production processes and internal control theory. The result achieved by analysis and design of accounting information systems production process is a desktop based application that can assist in the activities of the production process, especially in the documentation and storage of transaction data, and produce reports in accordance with company requirements. Conclusions derived from the analysis and design is the implementation of a desktop based application that can help PT XYZ to improve systems and procedures, so it can obtain the required information on time and accurately.